2014
DOI: 10.1111/bph.12443
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin inhibits the growth of Dictyostelium and MDCK‐derived cysts in a TRPP2 (polycystin‐2)‐dependent manner

Abstract: BACKGROUND AND PURPOSE Identifying and characterizing potential new therapeutic agents to target cell proliferation may provide improved treatments for neoplastic disorders such as cancer and polycystic diseases. EXPERIMENTAL APPROACH We used the simple, tractable biomedical model Dictyostelium to investigate the molecular mechanism of naringenin, a dietary flavonoid with antiproliferative and chemopreventive actions in vitro and in animal models of carcinogenesis. We then translated these results to a mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
0
43
1
Order By: Relevance
“…There are many potential mechanisms behind this effect. Dictyostelium is a well-studied model for cell movement (Dang et al, 2013;Artemenko et al, 2014) and has been explored in a range of pharmacological studies for identifying chemical targets (Robery et al, 2013;Waheed et al, 2014;Lockley et al, 2015). Indeed, a large number of studies have identified changes in cell behavior (particularly in movement) caused by deletion of individual proteins (Chattwood et al, 2014;Fets et al, 2014;Wessels et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many potential mechanisms behind this effect. Dictyostelium is a well-studied model for cell movement (Dang et al, 2013;Artemenko et al, 2014) and has been explored in a range of pharmacological studies for identifying chemical targets (Robery et al, 2013;Waheed et al, 2014;Lockley et al, 2015). Indeed, a large number of studies have identified changes in cell behavior (particularly in movement) caused by deletion of individual proteins (Chattwood et al, 2014;Fets et al, 2014;Wessels et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is provided by a recent study investigating novel targets of a standard strong bitter tastant, phenylthiourea (PTU), in Dictyostelium, where the bitter tastant inhibited cell movement (Robery et al, 2013), and a genetic screen identified a PTU-sensitive receptor with homology to a poorly characterized human GABAB protein, where the human protein restored the sensitivity to PTU in Dictyostelium (Robery et al, 2013). Another study, again in Dictyostelium, identified an ion channel (PDK2) to be targeted by a bitter taste-related compound, naringenin (Glendinning, 1994), a flavonoid found in high levels in citrus fruit (Waheed et al, 2014). This study also confirmed the conserved flavonoid-PDK2 interaction in mammalian (kidney) cells and proposed a therapeutic treatment for genetic mutations in the target through naringenin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, such compound specificity was described previously for the activities of plant polyphenols: only a subset of flavonoids affects the transport of the plant hormone auxin, and thus plant development [6,8,9]. The biomedical literature has recently begun to follow suit, with reports of particular polyphenolic secondary metabolites acting via individual protein targets and reaching distinct subcellular compartments [10,11]. There is also limited evidence for some pathways of flavonoid metabolism in humans, namely glucuronidation, o -methylation, and addition of glutathione, depending on where the compounds are absorbed [12].…”
Section: Introductionmentioning
confidence: 97%
“…Naringenin (4,5,7-trihydroxyflavanone) reduced cyst formation in both animal and in vitro studies of polycystic kidney disease (PKD): indeed, its action via the PKD2 protein was first demonstrated in the model microbe Dictyostelium [11]. Furthermore, naringenin, kaempferol and quercetin (3,3,4,5,7-pentahydroxyflavone) have been reported to inhibit phosphoinositide 3-kinase, nuclear factor B pathway and kinases involved in pro-apoptic signaling in cancer cells [17,18].…”
Section: Introductionmentioning
confidence: 99%